IMPLEMENTATION OF THE LITERACY ACTION LEARNING MODEL IN IMPROVING DATA AND DIGITAL LITERACY OF STUDENTS IN QUR'AN HADITS SUBJECT AT MI ISLAMIYAH BANJARPOH NGORO JOMBANG - Masita, Azza; Hanifuddin, Hanifuddin; Hosna, Rofiatul; Kibtiyah , Asriana (Jurnal Konseling Pendidikan Islam, 2025)
This study aims to analyze and describe the application of the Pasti Aksi Hanifida learning model in improving literacy and digital literacy of students in Al-Qur'an Hadith subjects at MI Islamiyah Banjarpoh. The background of this study is based on learning conditions that tend to still use conventional methods such as lectures, which are less effective in stimulating students' interest and active participation. The Pasti Aksi Hanifida learning model is an innovation that integrates students' physical, emotional, and creative potential through an active and collaborative approach. This study used a qualitative approach with a case study method. Data collection techniques were conducted through observation, interviews, and documentation, which were analyzed using domain, taxonomy, and component approaches. The findings indicate that the implementation of the Hanifida's Pasti Aksi model is capable of creating a more lively, enjoyable, and meaningful learning atmosphere. Students showed significant improvements in their reading comprehension skills, summarizing through mind mapping and concept maps, and presenting their learning outcomes through digital media such as PowerPoint and Canva. Teachers act as facilitators who guide students in the process of knowledge construction and the strengthening of 21st-century skills. Challenges in implementing this model, such as limitations in digital devices and teacher readiness, can be addressed through training and internal collaboration. Overall, the Hanifida Pasti Aksi model has proven effective in supporting innovative and transformative learning, particularly in the context of Islamic education in the digital age.